Fractional amplitude of low-frequency fluctuations in right dorsal cingulum bundle associated with depression symptoms in AD patients: effects of donepezil intervention - Guo, Zhongwei; Wei, Fuquan; Hou, Hongtao; Liu, Xiaozheng (Neurological sciences, 2025)
Objectives Our aim was to investigate the mechanisms of spontaneous brain activity of white matter functional signals in Alzheimer’s disease (AD) patients after donepezil intervention. Methods We used resting-state functional magnetic resonance imaging and the fractional amplitude of low-frequency fluctuations (fALFF) approach to investigate changes in spontaneous brain activity of white matter functional signals in AD patients before and after donepezil intervention. A total of 32 subjects participated in the study, including 16 healthy subjects (HCs) and 16 AD patients. The 16 AD patients underwent brain imaging and neuropsychological assessment before and after donepezil. ANOVA and post hoc t-test analysis were used to compare the differences in fALFF between the three groups. Pearson correlations were used to investigate the relationships between abnormal fALFF values and clinical variables in AD patients before and after intervention ( P < 0.05). Results Compared to HCs, AD patients before donepezil intervention had an abnormal fALFF in superior longitudinal fasciculus 2; AD patients after donepezil intervention had an abnormal fALFF in right superior longitudinal fasciculus 1,2 and right dorsal cingulum, Compared with baseline, AD patients after donepezil intervention had an abnormal fALFF in the right dorsal cingulum. Compared with the baseline, AD patients after donepezil intervention had significantly decreased depression scores ( P < 0.0003). Conclusions Our study showed that spontaneous activity of functional signalling in the cholinergic pathway was altered in AD patients after donepezil intervention and that this change was associated with depressive symptoms in AD patients.